2022
DOI: 10.3389/fendo.2022.1041889
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux related changes after sleeve gastrectomy and sleeve gastrectomy with fundoplication: A retrospective single center study

Abstract: BackgroundThe worsening of gastroesophageal reflux disease (GERD) and “de novo” GERD after laparoscopic sleeve gastrectomy (LSG) is a major concern as it affects the patient’s quality of life; the incidence of GERD after LSG is up to 35%. Laparoscopic sleeve gastrectomy with fundoplication (LSGFD) is a new procedure which is considered to be better for patients with morbid obesity and GERD, but there is a lack of objective evidence to support this statement. This study aimed to assess the effectiveness, safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, the weight loss mechanism following SGFD may be associated with a decrease in stomach capacity and the alteration of eating habits, as food passes through the gastroesophageal junction at a slower pace after gastric folding. Additionally, the research team’s previous investigations have shown remarkable weight loss effects of gastric fundus folding anti-reflux surgery [ 7 ]. We found an interesting phenomenon in the changes of blood sugar and triglyceride after SGFD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the weight loss mechanism following SGFD may be associated with a decrease in stomach capacity and the alteration of eating habits, as food passes through the gastroesophageal junction at a slower pace after gastric folding. Additionally, the research team’s previous investigations have shown remarkable weight loss effects of gastric fundus folding anti-reflux surgery [ 7 ]. We found an interesting phenomenon in the changes of blood sugar and triglyceride after SGFD.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Hiatal hernia (HH) prior to surgery further increases the risk of postoperative GERD. Recent studies by the author’s research team have demonstrated that laparoscopic fundoplication with sleeve gastrectomy (LFDSG) can effectively manage body weight and mitigate reflux symptoms [ 7 ]. The remission rate of reflux symptoms in patients who underwent SGFD can reach 86.4% one year after operation and 90.9% after an average follow-up of 34 (22–48) months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data show that associating ARB-enhancing techniques during the LSG could prevent de novo or worsening GERD. 29,34,55 Therefore, it is reasonable to assume those procedures act by physiologically separating the proximal stomach and the esophagus, restoring, in part, the esophagogastric motor function.…”
Section: Surgical Aspect: Tight Stapling Line and Resection Of The Gr...mentioning
confidence: 99%
“…This report presents a case of acute incarcerated hiatal hernia with partial volvulus due to ITSM in a patient who underwent concomitant hiatal hernia repair with LSG. [1][2][3][4][5][6][7][8][9][10][11]…”
Section: Introductionmentioning
confidence: 99%